ETIKA DALAM PENERAPAN STANDAR OPERASIONAL KEPROTOKOLAN GUBERNUR PROVINSI BENGKULU - Putera, Dento; Aprianty, Henny; Dani, Rahiman (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
Protocol is an important aspect in the implementation of government, especially in official activities involving regional heads such as governors. Protocol includes procedures, rules and customs that regulate official events, visits, receiving guests and other activities. The main purpose of protocol is to create an orderly, regular and solemn atmosphere, and reflect the authority and positive image of the regional government. Ethics are behavior, actions, self-image of the community towards the government, organization, or institution and individuals, an impression that is deliberately created from an object, person or organization. Ethics is one of the most important assets of an organization or individual that is deliberately created to have positive value. One of the government organizations that applies ethics in its application is the protocol. This study aims to analyze how ethics in the operational standards of the Bengkulu Province governor's protocol by reviewing the application of operational standards, ethics applied in the operational standards of protocol, identifying factors that influence the application of ethics, and efforts that can be made to improve ethics in the operational standards of protocol. The research method used is a qualitative approach with a descriptive method. Data were obtained through in-depth interviews with protocol staff and related officials, direct observation at official events, and documentation studies of protocol regulations and reports. Data analysis was carried out using data reduction techniques, data presentation, and conclusions to obtain a more comprehensive picture. This study is expected to contribute to the development of protocol policies in local government environments, as well as become a reference for further research in the field of public administration and government communication.